ANALISIS PEMBINAAN PRESTASI OLAHRAGA TENIS LAPANGAN DI KABUPATEN SAMPANG TAHUN 2018 - SYUKRON, AKHMAT; KHAMIDI, AMROZI (Jurnal Prestasi Olahraga, 2019)
Abstract Sport is one form of activity in the quality of Indonesian people that is directed at the formation of character and personality, high discipline and sportsmanship, and improvement in achievement that can increase a sense of national pride. In fostering the achievements of tennis sports Training and coaching of Tennis Courts which is a form of effort to create outstanding players. This study discusses the discussion of the achievements of field tennis sports in Sampang Regency in 2018 This type of research is qualitative research. Techniques for analyzing data using interviews. The research sample was 1 person Ikhsan had been a coach and caretaker for many years in the best field tennis in Sampang. The data analysis technique used in this study is a qualitative method which is intended as a research that produces descriptive data consisting of written words from people and those analyzed. The research results obtained in terms of selecting athletes by providing information about the holding of a traffic tennis championship in Sampang Regency, and information provided throughout schools, tennis clubs, institutions to attract participants (prospective tennis athletes in Sampang Regency) for training to support the program exercises such as comprehensive, proportional, building evidence. The facilities and infrastructure owned by PELTI in Sampang Regency are only one field More about further research More about developing research on fostering achievements in the field of tennis sports. Keywords: achievement coaching, tennis, coaches, athletes